Ethical problems experienced by nurses in primary health care: integrative literature review - Carlise Rigon Dalla Nora; Elma Lourdes Campos Pavone Zoboli; Margarida Vieira
The aim of this study is to identify ethical problems experienced by nurses in primary health care and resources for coping based on publications on the subject. An integrative literature review was performed between the months of October and November 2013, using the databases: BDTD, CINAHL, LILACS, MEDLINE, Biblioteca Cochrane, PubMed, RCAAP and SciELO. Articles, dissertations and theses published in Portuguese, English and Spanish were included, totalling 31 studies published from 1992 to 2013. This analysis resulted in four categories: ethical problems in the relationship between team members, ethical problems in the relationship with the user, ethical problems in health services management and resources for coping with ethical problems. Results showed that nurses need to be prepared to face ethical problems, emphasizing the importance of ethics education during the education process before and during professional practice to enhance the development of ethical sensitivity and competence for problem resolution.